Educational Assistance Program Management: An Integrated Approach to Planning, Implementation, Monitoring, and Evaluation - Annisa; Zainullah; Nur Hayati (Al-Qalam Institue, 2026)
This study aims to analyze the management of the Program Indonesia Pintar (PIP) by examining the processes of planning, implementation, monitoring, and evaluation within an educational institution. A qualitative descriptive research design was employed to obtain a comprehensive understanding of program management practices in their natural setting. Data were collected through observations, semi-structured interviews, and document analysis involving school administrators, program operators, teachers, parents, and student beneficiaries. The data were analyzed through data condensation, data display, and conclusion verification to identify patterns and themes related to program implementation. The findings reveal that the program has been managed systematically through beneficiary identification, administrative verification, coordinated fund distribution, and continuous monitoring of fund utilization. Nevertheless, several challenges remain, including delays in fund disbursement, incomplete administrative records, limited parental understanding of program procedures, and coordination issues among relevant stakeholders. The study implies that strengthening data management, improving stakeholder coordination, expanding communication with parents, and reinforcing monitoring and evaluation mechanisms are essential to enhance the effectiveness, transparency, and accountability of educational assistance program management.